PERBAIKAN YANG PERLU DILAKUKAN DALAM PENERAPAN PERSONNEL DAN CULTURAL CONTROL BERBASIS FILOSOFI KEPEMIMPINAN HASTA BRATA UNTUK MENGATASI CONTROL PROBLEM PADA PO “MAHKOTA” DI KEDIRI. - Sukma Indah Pratiwi (Perpustakaan Universitas Surabaya, 2016)
This research intends to explain and predict the relationship between philosophy of leadership and informal control systems to solving control problem. this research has the goal to find out how leadership’s philosophy of Hasta Brata affect the application of informal control system. The existence of informal control system which is influenced by the philosophy of leadership that can solve the control problem. This research is applied research with a qualitative approach. This research seek to provide recommendations for control and troubleshoot problems, that need to improve implementation of the informal control system and leadership of philosophy Hasta Brata at PO